Vitamin D and chronic kidney disease: Insights on lipid metabolism of tubular epithelial cell and macrophages in tubulointerstitial fibrosis - Gonçalves, Luís Eduardo D.; Andrade-Silva, Magaiver; Basso, Paulo José; Câmara, Niels O. S. (Frontiers in Physiology, 2023)
Chronic kidney disease (CKD) has been recognized as a significant global health problem due to being an important contributor to morbidity and mortality. Inflammation is the critical event that leads to CDK development, and complex interactions between renal parenchyma and immune cells orchestrate them. Particularly, the crosstalk between tubular epithelial cells (TECs) and macrophages is an example of the critical cell communication in the kidney that drives kidney fibrosis, a pathological feature in CKD. Metabolism dysregulation of TECs and macrophages can be a bridge that connects inflammation and fibrogenesis. Currently, some evidence has reported how cellular lipid disturbances can affect kidney disease and cause fibrosis highlighting the importance of investigating potential molecules that can restore metabolic parameters. Vitamin D (VitD) is a hormone naturally produced by mammalian cells in a coordinated manner by the skin, liver, and kidneys. VitD deficiency or insufficiency is prevalent in patients with CKD, and serum levels of VitD are inversely correlated with the degree of kidney inflammation and renal function. Proximal TECs and macrophages produce the active form of VitD, and both express the VitD receptor (VDR) that evidence the importance of this nutrient in regulating TECs and macrophage function. However, whether VitD signaling drives the metabolism improvement of TECs and macrophages during kidney injury is an open issue to be debated. In this review, we brought to light VitD as an important metabolic modulator of lipid metabolism in TECs and macrophages. New scientific approaches targeting VitD e VDR signaling at the cellular metabolic level can provide a better comprehension of its role in renal physiology and CKD progression.